Optimum waist circumference‐height indices for evaluating adult adiposity: An analytic review. (10th September 2019) - Hwaung, Phoenix; Heo, Moonseong; Kennedy, Samantha; Hong, Sangmo; Thomas, Diana M.; Shepherd, John; Heymsfield, Steven B.
Summary: Phenotyping adults for excess adiposity and related health risks usually include three body size measurements: height, weight and waist circumference (WC). Height and weight are now widely used as components of the body shape measure, body mass index (BMI, weight/height 2 ), with the height power referred to as the scaling factor, α. At present, WC is usually not adjusted for height or is expressed as WC/height in which α = 1. Although other α values have been proposed, a critical review of these shape measures is lacking. Here, we examine classical pathways by which the scaling exponent for height used in BMI was developed and then apply this strategy to identify the optimum WC index characteristic of adult shape. Our analyses explored anthropometric, body composition and clinically‐relevant data from US and Korean National Health and Nutrition Surveys. Our findings provide further support for the WC index of WC/height 0.5 as having the strongest associations with adiposity while having the weakest correlations with height across non‐Hispanic white and black, Mexican American and Korean men and women. The WC index, defined as WC/height 0.5, when combined with BMI, can play an important role when phenotyping adults for excess adiposity and associated health risks in research and clinical settings.